A chiral smectic structure assembled from nanosheets and nanorods. Issue 11 (23rd January 2017) - Pan, H.; Zhu, C.; Lu, T.; Lin, J.; Ma, J.; Zhang, D.; Zhu, S.
Abstract : A chiral smectic structure assembled from nanosheets and nanorods should open a new route to create a variety of chiral structures. Abstract : Here we report a novel chiral smectic through self-assembling two-dimensional graphene oxide nanosheets and one-dimensional cellulose nanorods. As shown by a phase diagram, the formation of the chiral smectic strictly depends on the ratio of nanosheets to nanorods as well as the concentration of the composite colloid. It would open up a new way for the development of mesoscopic materials with tunable physical properties, such as optical metamaterials with application in optical modulation and mechanochromic sensors.